2015
DOI: 10.1007/s11627-015-9677-x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding new seedless grapes using in ovulo embryo rescue and marker-assisted selection

Abstract: A program for producing new seedless table and raisin grape cultivars was initiated using embryo culture methods. F 1 descendants of the cross Delight × Ruby Seedless (DRs) were used as the female parent and crossed with various seedless cultivars. The berries of DRs have excellent table traits but they retain small seed traces at maturity. Blush Seedless and DRs were used as female parents, and 354 ovules from five crosses were tested. The percentage of embryos that developed using DRs as the female parent wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
0
29
1
Order By: Relevance
“…Ramming et al (2000) obtained a stenospermic hybrid (C41-5, interspecies cross V. vinifera × V. rotundifolia) by embryo rescue. Our group has access to Chinese wild Vitis spp., which have strong resistance to fungal diseases and to cold, and crossed these with V. vinifera to develop new, disease-resistant and cold-resistant seedless grapes (He & Chao 1982;Wang et al 1998;Tian et al 2008;Tang et al 2009;Ji et al 2013;Li GR et al 2013;Li ZQ et al 2015). In 2005, we released a new disease-resistant seedless cultivar 'Qinhong Seedless' .…”
Section: Results Of the Identification Of Seedlessness Charactermentioning
confidence: 99%
See 3 more Smart Citations
“…Ramming et al (2000) obtained a stenospermic hybrid (C41-5, interspecies cross V. vinifera × V. rotundifolia) by embryo rescue. Our group has access to Chinese wild Vitis spp., which have strong resistance to fungal diseases and to cold, and crossed these with V. vinifera to develop new, disease-resistant and cold-resistant seedless grapes (He & Chao 1982;Wang et al 1998;Tian et al 2008;Tang et al 2009;Ji et al 2013;Li GR et al 2013;Li ZQ et al 2015). In 2005, we released a new disease-resistant seedless cultivar 'Qinhong Seedless' .…”
Section: Results Of the Identification Of Seedlessness Charactermentioning
confidence: 99%
“…However, the 198-bp allele has also been found in several seeded cultivars. Another SCAR marker linked to grape seedlessness is GSLP1-569 (Wang & Lamikanra 2002;Yang et al 2005), which has been used to select seedless progenies (Tian et al 2008;Ji et al 2013;Li ZQ et al 2015). Murat et al (2013) used different molecular markers to select seedless individuals in F 1 hybrids, the results showed that the identification results were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…"Prime", "Mystery", "Spring Blush" and "Black-finger" are seedless table grape cultivars developed in Israel (Perl et al, 2003). Similarly, many studies have been published in the literature reporting the successful use of the embryo rescue technique in crossbreeding studies in viticulture (Ramming et al, 2000;Yang et al, 2007;Tian & Wang, 2008;Ji & Wang, 2013;Uquillas et al, 2013;Li et al, 2014Li et al, , 2015.…”
Section: Conventional Crossbreedingmentioning
confidence: 99%